(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
This article reveals the essence of the concept of competence. Ways to pedagogically develop professional competence of learners are shown. The content of the set of competencies, which determines the level of development of pedagogical competence that can be acquired for future teachers, is highlighted